Designing Gadolinium-doped ceria electrolyte for low temperature electrochemical energy conversion. (30th April 2023) - Shah, M.A.K. Yousaf; Lu, Yuzheng; Mushtaq, Naveed; Yousaf, Muhammad; Lund, Peter D.; Asghar, Muhammad Imran; Zhu, Bin
Abstract: Reducing the operational temperature of solid oxide fuel cells (SOFC) is vital to improving their durability and lifetime. However, a traditional SOFC suffers from high ohmic and polarization losses at low temperatures, leading to poor performance. Gadolinium-doped ceria is the best ionic conductor for SOFC at lower temperatures. The present work envisages the GDC as an electrolyte for applying low-temperature solid oxide fuel cells (LT-SOFCs). So, in this regard, herein, GDC is synthesized through a wet chemical co-precipitation technique as a functional electrolyte layer fixed between two symmetrical porous electrodes NCAL (Ni0.8 Co0.15 Al0.05 LiO2 ). Due to the improved surface properties of the synthesized GDC, particles perform better than commercially available GDC. The synthesized GDC electrolyte shows an impressive fuel cell performance of 569 mW/cm 2 and a high ionic conductivity of 0.1 S/cm at a shallow temperature of 450 °C. Moreover, the fuel cell device utilizing the synthesized GDC remained stable for 150 h of operation at a high current density of 110 mA/cm 2 at 450 °C. The high conduction mechanism has been proposed in detail. The results show that excellent fuel cell performance, high ionic conductivity, and better stability can be achieved at exceptionally low enough temperatures. Also, the proposed work suggests that new electrolytes can be designed for developing advanced low-temperature fuel cell technology. Graphical abstract: Image 1 Highlights: Gadolinium-doped ceria is synthesized through a wet chemical co-precipitation technique. The synthesized GDC electrolyte exhibits a high ionic conductivity of 0.1 S/cm at 450 °C. The fuel cell using the synthesized GDC produced 569 mW/cm 2 at 450 °C . The fuel cell device remained stable for 150 h at a high current density of 110 mA/cm 2 .